The effect of parenting training program on depression, anxiety and stress of mothers of children with attention deficit / hyperactivity disorder - M Hosseini Nejad; Z Karimi; KH Nourian; L Manzoori; M Zol-Adl (Armaghane Danesh Bimonthly Journal, 2020)
Background & aim: Living with children suffering from Attention-Deficit / Hyperactivity Disorder may lead to significant psychological problems such as stress, anxiety, and depression for their parents. For decreasing these problems, using psychological interventions is necessary. Therefore, the present study aimed to determine the effect of a parenting education program on depression, anxiety, and stress of mothers with Attention-Deficit / Hyperactivity Disorder children.